Hemodialysis prophylaxis and renal replacement therapy in contrast associated acute kidney injury (CA-AKI): literature study - Satwikajati, Sawitri; Novi Kurnianingsih (Universitas Brawijaya, 2025)
Contrast associated acute kidney injury (CA-AKI) had been the main focus along the development of percutaneous invasive procedure. Contrast associated acute kidney injury (CA-AKI) increase risk of dead among hospitalized patient. The use of iodine based contrast along percutaneous procedure potentially induce contrast associated acute kidney injury (CA-AKI). Many potential hazardous effect may effect individual with CA-AKI such as myocardial re-infarction, stent thrombosis, dead, and major adverse cardiac event (MACE). Many strategies had been developed to prevent and treat CA-AKI such as risk stratification, hydration with normal saline, avoid nephrotoxic drug, use of statin, and N-acetilcystein but when all strategies failed, hemodialysis prophylaxis and renal replacement therapy had potential benefit in CA-AKI.